Avaliações socioeconômicas e ambientais da bovinocultura de leite: o caso dos projetos de reforma agrária no noroeste Rio-Grandense - Paris, Julio Cesar (2015)
The northwestern region of Rio Grande do Sul has stood out in recent years by the dynamic evolution of the dairy farming, forming together with the Center-West of Santa Catarina and southwest of Paraná the new axis of territorial concentration of milk production. The small rural establishments, including the settlement and resettlement projects of agrarian reform, has contributed greatly to the growth of production and supply of this food, as well as possible the permanence and the social reproduction of countless families who would be doomed to deletion due to the advancement of a grain producer and commodity model. The present study aimed to analyze agrarian reform projects of the Operational Core of Palmeira das Missões and the prevailing of dairy production systems describing economic, social and environmental indicators seeking to understand the logic of operation of these productive units, moving beyond the economic, noting the occurrence of environmental problems and constraints of family labor. It was also necessary to characterize the territory the milk supply chain, marketing and organization dynamics of families. From the systemic method, on the basis of the theory of Agrarian Systems ne, or Diagnostic Analysis of Agricultural Systems studied four types of family production systems identified by rural extension workers of Emater/RS-Ascar working in technical and Social assistance program in the core of Palmeira das Missões. After describing the different types, socio-economic and environmental evaluation was performed of the lots, where it was possible to observe that despite the economic viability, all types have more or less severe constraints of manpower, not only with respect to availability, but the painfulness of the dairy activity, still it was possible to identify limits the exploitation of nature due to various signs of environmental degradation observed.